ROOTS PROGRAM UTILITY; FORMING AN ANTI BULLYING PREVENTION AGENT IN MADRASAH - Junaedi, Achmad (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2023)
This study aimed to determine the efforts of teachers to apply interactional teaching style as an interdiscipliner approach to identify student learning characteristics. This research included phenomenological research with a qualitative approach. The research location was conducted at MTs. NU, Kraksaan District, Probolinggo. Data collection techniques were carried out through a process of observation, in-depth interviews with 4 informants, and documentation. The data analysis technique used the Miles and Huberman Interactive Model with data reduction activities, data presentation, and drawing conclusions. Data validity with source and technique triangulation process. The process undertaken in the Roots program included several stages, namely conducting surveys, selecting agents of change, providing training to agents of change, carrying out demonstrations or social campaigns in the madrasah environment, and evaluating the Roots program. Of course the Roots program has been carried out according to the plan and systematic program of activities and of course the agents of change can synergize themselves as actors driving students' understanding and concern about stop-bullying in the madrasah environment. The implications of the research illustrated that collaboration between madrasahs, facilitators, agents of change, and students is established in a supportive manner and upholds the value of tolerance.